Photoperiod and vernalization requirements in Argentinian oat genotypes - Dietz, Juan Ignacio; Da Silva, Laura Victoria; Schierenbeck, Matías; Pardi, Martín; Simón, María Rosa (Wiley, 2025)
Understanding the response to temperature, vernalization, and photoperiod provides a significant advantage for optimizing the adaptability of oat (Avena sativa) genotypes to different production areas and sowing seasons in a climate change context. For this, two experiments were carried out in the Argentinian Pampas, where nine oat genotypes were sown on six sowing dates (from June to December, <10 h to >15 h photoperiod) and three vernalization treatments (40, 20, and 0 days at 4°C). Days from emergence to flowering were evaluated and then converted to growing degree days. The adjustment of duration from emergence to flowering using an average photoperiod was performed using bilinear regressions to determine the photoperiod sensitivity (Ps), threshold (Pt), and earliness per se. Our findings showed that genotypes were insensitive to vernalization, others with minimal requirements (<480 cold hours at 4°C) while materials with high requirements were not found, indicating a reasonably constrained range of variability. Different photoperiod responses were found between the genotypes explained by differences in Ps (slopes from −310°C days h−1 to −158°C days h−1) and Pt. Overall, vernalization was not strictly necessary for flowering across all genotypes or sowing dates, but its fulfillment significantly accelerated developmental transitions under long-day conditions.